High sensitivity ultra-broad-band absorption spectroscopy of inductively coupled chlorine plasma. (20th April 2016) - Marinov, Daniil; Foucher, Mickaël; Campbell, Ewen; Brouard, Mark; Chabert, Pascal; Booth, Jean-Paul
Abstract: We propose a method to measure the densities of vibrationally excited Cl2 ( v ) molecules in levels up to v = 3 in pure chlorine inductively coupled plasmas (ICPs). The absorption continuum of Cl2 in the 250–450 nm spectral range is deconvoluted into the individual components originating from the different vibrational levels of the ground state, using a set of ab initio absorption cross sections. It is shown that gas heating at constant pressure is the major depletion mechanism of the Cl2 feedstock in the plasma. In these line-integrated absorption measurements, the absorption by the hot (and therefore rarefied) Cl2 gas in the reactor centre is masked by the cooler (and therefore denser) Cl2 near the walls. These radial gradients in temperature and density make it difficult to assess the degree of vibrational excitation in the centre of the reactor. The observed line-averaged vibrational distributions, when analyzed taking into account the radial temperature gradient, suggest that vibrational and translational degrees of freedom in the plasma are close to local equilibrium. This can be explained by efficient vibrational-translational (VT) relaxation between Cl2 and Cl atoms. Besides the Cl2 ( v ) absorption band, a weak continuum absorption is observed at shorter wavelengths, and is attributed to photodetachment of Cl − negative ions. Thus, line-integrated densities of negative ions in chlorine plasmas can be directly measured using broad-band absorption spectroscopy.